Discovery of Electricity and the Electromagnetic Force: Its Importance for Environmentalists, Educators, Physicians, Politicians, and Citizens - Baldwin, Ian (Advances in Social Sciences Research Journal, 2020)
The discovery of static electricity in the 18th century and electromagnetism in the 19th was one of the most momentous scientific-technological events in human history. In the 21st century our way of life depends on the electromagnetic force so totally that were our electromagnetic infrastructure to collapse, our civilization would collapse virtually simultaneously. Despite this situation of profound dependency, few citizens understand the electromagnetic force, how it was discovered, how it works, and what wonders of modern life it controls. Nor do citizens understand the roles that Earth’s magnetosphere, ionosphere, and global electric circuit play in making electricity and life possible. Here, I review Earth’s natural electric environment and how electricity first began to be scientifically understood with the innovation of the Leyden jar in the mid-18th century; Franklin’s insights about electricity’s positive and negative poles, and its movement (later named a “current”); Galvani’s discovery of bioelectricity; and Volta’s seminal invention of the bi-metallic electrochemical battery in 1800. Ørsted’s discovery that an electric current affected a magnetized needle, causing it to swivel, in 1820 led to experiments with electromagnets by Schweigger, Arago, Ampère, Sturgeon, Henry, Faraday, and others over the course of the next decade. Observing how conducting wires induced magnetism in iron bars whenever the wires were electrified, Faraday and Henry separately discovered the principle of induction, whereby a moving magnetic field could reciprocally induce electricity in a coiled wire. Out of these momentous discoveries the “magneto-electric” telegraph was invented, and, within a single generation, the world was wired.